Program for the Education and Enrichment of Relational Skills for adolescents with an acquired brain injury: A randomized controlled trial. (28th January 2022) - Gilmore, Rose; Ziviani, Jenny; Mcintyre, Sarah; Smithers Sheedy, Hayley; Hilton, Nicola; Williams, Tracey; Chatfield, Mark D.; Laugeson, Elizabeth; Sakzewski, Leanne
Abstract : Aim: To test the efficacy of a group social skills intervention on social functioning in adolescents with a brain injury. Method: Thirty‐six adolescents (mean age 14y, SD 1y 8mo, age range 12y 1mo–16y 3mo; 17 females) with acquired brain injury (ABI; ≥12mo postintervention; n =19) or cerebral palsy ( n =17) were randomly allocated to the Program for the Education in Enrichment of Relational Skills (PEERS) or usual care. The primary outcome was the Social Skills Improvement System‐Rating Scales (SSIS‐RS). Secondary outcomes were scores derived from the Test of Adolescent Social Skills Knowledge‐Revised (TASSK‐R), Social Responsiveness Scale, Second Edition, and Quality of Socialization Questionnaire. Between‐group differences postintervention and at the 26‐week retention time point were compared using linear mixed modelling for continuous outcomes and Poisson regression for count data. Results: There were no between‐group differences on the primary outcome (SSIS‐RS). Regarding the secondary outcomes, the PEERS‐exposed group achieved significantly greater improvements on the TASSK‐R (mean difference [MD]=6.8, 95% confidence interval [CI]=4.8–8.8, p <0.001), which were maintained at the 26‐week retention time point (MD=8.1, 95% CI=6.0–10.2, p <0.001). PEERS was also associated with a significant increase in parent‐reported invited get‐togethers at 26 weeks (incidence rate ratio=4.0, 95% CI=1.0–16.0, p =0.05). Interpretation: Adolescents with brain injury who completed the PEERS learned and retained social knowledge and increased social participation.